Recruitment of histone deacetylases HDAC1 and HDAC2 by the transcriptional repressor ZEB1 downregulates E-cadherin expression in pancreatic cancer. Issue 3 (5th December 2011) - Aghdassi, Ali; Sendler, Matthias; Guenther, Annett; Mayerle, Julia; Behn, Claas-Olsen; Heidecke, Claus-Dieter; Friess, Helmut; Büchler, Markus; Evert, Matthias; Lerch, Markus M; Weiss, Frank Ulrich
Abstract : Objective: Pancreatic cancer is characterised by invasive tumour spread and early metastasis formation. During epithelial–mesenchymal transition, loss of the cell adhesion molecule E-cadherin is frequent and can be caused by genetic or epigenetic modifications, recruitment of transcriptional activators/repressors or post-translational modifications. A study was undertaken to investigate how E-cadherin expression in human pancreatic adenocarcinoma and pancreatic cancer cell lines is regulated. Methods: In 25 human pancreatic cancer resection specimens, the coding region of the E-cadherin gene (CDH1) was sequenced for somatic mutations. The tumour samples and 11 established human pancreatic cancer cell lines were analysed by immunohistochemistry, western blot analysis, chromatin immunoprecipitation and methylation-specific PCR. The role of specific histone deacetylase inhibitors (HDACi) on pancreatic tumour cell migration and proliferation was studied in vitro. Results: Neither somatic mutations nor CDH1 promoter hypermethylation were found to be responsible for downregulation of E-cadherin in pancreatic cancer. In the transcriptionally active CDH1 promoter, acetylation of histones H3 and H4 was detected whereas HDAC1 and HDAC2 were found attached only to a silent promoter. Expression of ZEB1, a transcription factor known to recruit HDACs, was seen in E-cadherin-deficient cell lines in which ZEB1/HDAC complexes were found attached to the CDH1 promoter. Moreover, knockdown of ZEB1 prevented HDAC from binding to the CDH1 promoter, resulting in histone acetylation and expression of E-cadherin. HDACi treatment attenuated tumour cell migration and proliferation. Conclusions: These findings imply an important role for histone deacetylation in the downregulation of E-cadherin in human pancreatic cancer. Recruitment of HDACs to the CDH1 promoter is regulated by the transcription factor ZEB1, and inhibition of HDACs may be a promising antitumour therapy for pancreatic cancer.